2020
DOI: 10.3389/fonc.2020.01544
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of microRNA Expression Profile in Chronic Myeloid Leukemia Patients Newly Diagnosed and Treated by Allogeneic Hematopoietic Stem Cell Transplantation

Abstract: Chronic myeloid leukemia (CML) results from a translocation between chromosomes 9 and 22, which generates the Philadelphia chromosome. This forms BCR/ABL1, an active tyrosine kinase protein that promotes cell growth and replication. Despite great progress in CML treatment in the form of tyrosine kinase inhibitors, allogeneic-hematopoietic stem cell transplantation (allo-HSCT) is currently used as an important treatment alternative for patients resistant to these inhibitors. Studies have shown that unregulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…These miRNAs act as onco-miRs or tumor suppressors and are increased in other cancer types ( Table 2 ). Previous studies on the expression pattern of miR-16-1 in newly diagnosed CML-CP treated with IM have shown that down-regulation of miR-16 can play important roles in myeloid leukemogenesis by regulating cell cycle and apoptosis, as well as targeting multiple oncogenes, including, BCL2, MCL1, CCND1, and WNT3A [32] . Inversely, in the present study and our previous experiment for CML, we surprisingly observed up-regulation of miR-16–1 in this particular disease state ( Fig.…”
Section: Discussionmentioning
confidence: 98%
“…These miRNAs act as onco-miRs or tumor suppressors and are increased in other cancer types ( Table 2 ). Previous studies on the expression pattern of miR-16-1 in newly diagnosed CML-CP treated with IM have shown that down-regulation of miR-16 can play important roles in myeloid leukemogenesis by regulating cell cycle and apoptosis, as well as targeting multiple oncogenes, including, BCL2, MCL1, CCND1, and WNT3A [32] . Inversely, in the present study and our previous experiment for CML, we surprisingly observed up-regulation of miR-16–1 in this particular disease state ( Fig.…”
Section: Discussionmentioning
confidence: 98%
“…The total RNA amount was determined by the ratios A 260 nm/A 280 nm and A 260 nm/A 230 nm (acceptable when both ratios were greater than 1.8). RNA integrity was ensured by obtaining an RNA integrity number (RIN > 8) using the Agilent 2100 Bioanalyzer (Agilent Technologies, Waldbronn, Germany) [ 65 , 66 ].…”
Section: Methodsmentioning
confidence: 99%
“…The reverse transcription reaction was performed using the Taqman MicroRNA Reverse Transcription Kit in combination with Megaplex RT Primer Human Pool Set A and B (Thermo Fisher Scientific, Waltham, MA, USA). This reaction transcribed 758 miRNAs and three positive endogenous controls (U6 snRNA, RNU44, and RNU48) and one negative control [ 65 , 66 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They act in several gene regulation processes that may end up in complex diseases, such as cancer [125]. The first suggestion that miRNAs are correlated to cancer was in 2002 [126,127], and since then miRNAs have been identified as essential switches in cancer pathology [128]. Moreover, deregulated miRNAs have oncogenic and/or tumor suppressive functional roles [129].…”
Section: Epigenetic Regulation In CMLmentioning
confidence: 99%